Identification of Diversity and Genetic Distance of Indonesian Local Chicken Strains Based on Myostatin Gene - Muhsinin, Muhammad; Maskur, Maskur; Jan, Rahma; Rozi, Tapaul; Kasip, Lalu Muhammad; Al Farizi, Muhammad Salman (Jurnal Biologi Tropis, 2025)
Indonesian local chickens are essential genetic resources with significant potential for advancing the national poultry industry due to their high genetic diversity, reflecting adaptation to tropical environments and traditional farming systems. This study analyzed the genetic diversity of Kampung, Sentul, KUB, SenSi, and Broiler chickens based on the MSTN g.4842T>G locus. Blood samples from 150 chickens underwent PCR-RFLP analysis using the BsrI restriction enzyme targeting exon 2 of the MSTN gene. Parameters such as observed heterozygosity (Ho), expected heterozygosity (He), polymorphism information content (PIC), and Hardy-Weinberg equilibrium were assessed. Genetic distances were calculated using PHYLIP, and a dendrogram was constructed with UPGMA. The study identified two alleles (G and T) and three genotypes (GG, GT, TT), with the T allele being dominant, particularly in Broiler chickens (78.3%). Ho was lower than He in all populations, indicating a heterozygosity deficit. PIC values ranged from 0.282 (Broiler) to 0.367 (SenSi), classifying the MSTN locus as moderately polymorphic. Kampung and KUB chickens showed the closest genetic relationship, while Broiler chickens were the most distinct. These findings underscore the potential of local chickens in breeding programs for adaptability and productivity. Further research with additional markers is recommended to enhance sustainable poultry farming.